Insulin resistance in ischemic stroke: Mechanisms and therapeutic approaches - Ding, Peng-Fei; Zhang, Hua-Sheng; Wang, Jie; Gao, Yong-Yue; Mao, Jian-Nan; Hang, Chun-Hua; Li, Wei (Frontiers in Endocrinology, 2022)
The pathological condition of insulin resistance prevents the neuroprotective effects of insulin. Numerous studies have demonstrated that insulin resistance, as an independent risk factor for ischemic stroke, accelerates the formation of thrombosis and promotes the development of atherosclerosis, both of which are major mechanisms of ischemic stroke. Additionally, insulin resistance negatively affects the prognosis of patients with ischemic stroke regardless of whether the patient has diabetes, but the mechanisms are not well studied. We explored the association between insulin resistance and the primary mechanisms of brain injury in ischemic stroke (inflammation, oxidative stress, and neuronal damage), looking for potential causes of poor prognosis in patients with ischemic stroke due to insulin resistance. Furthermore, we summarize insulin resistance therapeutic approaches to propose new therapeutic directions for clinically improving prognosis in patients with ischemic stroke.